Language Production among Multilingual Children: Insights on Code Mixing - Maria Klara Timorina Situmorang; Umar Mono; Alemina Br Perangin-angin (Jurnal Bahasa dan Sastra, 2023)
Code mixing is a common phenomenon in today's society, occurring in various settings such as schools, buses, and offices. This refers to the use of more than one language element (code) by multilingual speakers. The purpose of this research is to identify the types and forms of code mixing used by students and to analyze the factors involved. Code mixing utterances are classified into three types: insertion, substitution, and congruence. This study uses a qualitative method to analyze code mixing among five multilingual students aged 4-5 years. The results showed that in one international school class there were 20 code-mixed utterances which involved mixing Mandarin, Indonesian into English. Of these incidents, 14 of them were insertion code mixing. This indicates that the most common type of code mixing among multilingual children is code insertion mixing, in which non-matrix language words and phrases (Chinese and Indonesian) are inserted into the matrix (English). This is due to the fact that the children come from different ethnic backgrounds and some speak Mandarin as their mother tongue.